Victorian Metafiction - Sparks, Tabitha (Book collections on Project MUSE., 2022)
"This book identifies the literary technique of metafiction in numerous novels by women writers (including Charlotte Brontë, Rhoda Broughton, Charlotte Riddell, and Eliza Lynn Linton) and argues that women used metafictional self-consciousness to draw the reader's attention to the book, and not the novelist. This counters a long-standing tradition that has read novels by women writers as heavily autobiographical and confessional"--